Rubber toughening of practical tetraglycidyl methylenedianiline-piperidine adduct systems - Pearce P J; Ennis B C; Morris C E M (Polymer, 1996)
The inherent brittleness of tetraglycidyl methylenedianiline (TGMDA) based epoxy formulations can be mitigated by the addition of carboxyl-terminated butadiene-nitrile rubbers (CTBNs) if piperidine is used as the curing agent. The problems of toxicity, reactivity and volatility associated with this reagent are overcome by using it in a latent form, as an amino alcohol or urea, after reacting it with a suitable epoxide or isocyanate. The fracture properties, measured by the critical strain energy release rate (GIc) and the critical stress intensity factor (KIc), of the new materials were compared to those of the TGMDA-diaminodiphenylsulfone (DDS) system. The best system gave GIc values up to 5.5 times those of the standard TGMDA-DDS formulation, while the addition of CTBN further increased this to up to 24 times; in comparison, addition of CTBN to the base formulation effected a threefold increase in GIc; there is however some lowering of the glass transition temperature and modulus of the modified resins. The morphology of the rubber-toughened materials, their reactivity, latency and water uptake are discussed.
Keywords: Piperidine; Rubber toughening; TGMDA